Retail Investor Surge in Response to Interest Rate Stability: A Case Study of the Indonesian Capital Market in 2025 - Reski Dwi Damayanti; Muchriana Muchran (CV. AFDIFAL MAJU BERKAH, 2025)
In 2025, the Indonesian capital market recorded a significant surge in retail investor participation, particularly following Bank Indonesia’s decision to maintain its benchmark interest rate at 5.75% for four consecutive quarters. This study aims to examine the shifting investment behavior of the public resulting from the stability of monetary policy. Using a quantitative-descriptive approach through secondary data analysis from the Indonesia Stock Exchange, online trading platforms, and surveys of retail investors, the findings indicate that interest rate stability encouraged investors to shift their funds from fixed-income instruments to riskier assets such as stocks. The technology, renewable energy, and domestic consumption sectors became the main investment targets, driven by economic optimism and the influence of social media. This phenomenon demonstrates that macroeconomic policy has a substantial impact on the dynamics of the retail capital market. However, the high reliance of investors on non-formal sources of information also introduces the risk of herd behavior and speculation, which should be addressed by regulators. This article recommends enhancing financial literacy and implementing technology-based supervision to ensure that the growth in retail participation remains healthy and sustainable.